Analisis Profitabilitas dan Likuiditas dalam Penilaian Kinerja Keuangan pada PT PLN (PERSERO) Periode 2020-2024 (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This study aims to analyze the development of profitability and liquidity ratios to assess the financial performance of PT PLN (Persero) during the 2020–2024 period. The research method used is descriptive quantitative, with data collection techniques in the form of documentation using secondary data obtained from the financial position report and annual income statement accessed through the company's official website. Profitability analysis focuses on measuring Return on Assets (ROA) as an indicator of the company's ability to generate profits from its total assets. Meanwhile, liquidity analysis uses the Current Ratio (CR) to measure the extent to which the company's current assets can cover its short-term liabilities. The results show that PT PLN (Persero)'s ROA has increased annually, although it remains below the industry average. This indicates increased efficiency in asset utilization, but not yet optimal profit generation. Meanwhile, the Current Ratio shows a fluctuating trend, but overall tends to increase from year to year. This indicates the company's ability to meet short-term obligations is improving and stable. Therefore, it can be concluded that PT PLN (Persero)'s financial performance during the study period has shown positive developments, although more effective strategies are still needed to increase profitability sustainably.